Negotiating Internet governance - Radu, Roxana (Oxford : Oxford University Press, 2019)
This monograph will analyse internet governance as an emerging issue domain, tracing the actors, institutions, and policies involved in its evolution as a global political construct over 40 years.
This edition previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 14, 2019).
Keywords: Internet -- Law and legislation; Law; Laws of specific jurisdictions & specific areas of law